2019
DOI: 10.1139/bcb-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of MAPT-AS1 is associated with better patient survival in breast cancer

Abstract: Breast cancer is the most frequent malignant disease in women worldwide. It is a heterogeneous and complex genetic disease with different molecular characteristics. MAPT-AS1, a long non-coding RNA(lncRNA) existing at the anti-sense strand of MAPT (microtubule associated protein tau) promoter region, was believed to regulate MAPT which was associated with disease state in Parkinson's disease. But the role of MAPT-AS1 in breast cancer has never been reported. In our study we found that MAPT-AS1 is overexpressed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 33 publications
3
28
0
Order By: Relevance
“…It might be involved in the EGFR/mammalian target of rapamycin pathway, which promoted triple negative breast cancer progression by affecting the stability of PTEN protein [31]. Previous study indicated the high expression of MAPT-AS1 was correlated with better survival in breast cancer [32]. However, we have not found any report about MIR4458HG related to breast cancer.…”
Section: Functional Prediction Of Three Lncrnasmentioning
confidence: 68%
“…It might be involved in the EGFR/mammalian target of rapamycin pathway, which promoted triple negative breast cancer progression by affecting the stability of PTEN protein [31]. Previous study indicated the high expression of MAPT-AS1 was correlated with better survival in breast cancer [32]. However, we have not found any report about MIR4458HG related to breast cancer.…”
Section: Functional Prediction Of Three Lncrnasmentioning
confidence: 68%
“…Additionally, MAPT-AS1 levels have been shown to be associated with MAPT expression, which is associated with breast cancer survival. The results of that study indicated that MAPT-AS1 may function as a potential breast cancer survival prediction biomarker (41). Pan et al (42) found that patients with ER-negative breast cancer who had larger tumors (≥2 cm), were of a younger age (<60), were at stages (III-IV) and had metastatic lymph nodes, exhibited higher levels of MAPT-AS1 expression.…”
Section: Discussionmentioning
confidence: 94%
“…MAPT-AS1 is involved in the occurrence and development of tumors and Parkinson's disease. MAPT-AS1 overexpression has not been found in breast cancer; however, in triple-negative type (TNBc), a high MAPT-AS1 expression has been found to be associated with a longer patient survival (41). Additionally, MAPT-AS1 levels have been shown to be associated with MAPT expression, which is associated with breast cancer survival.…”
Section: Discussionmentioning
confidence: 99%
“…1 , a total of 31 articles published between 2015 and 2020 with 3146 TNBC patients were included in this meta-analysis. The 27 relevant lncRNAs were as follows: LINC00096, [ 11 ] SNHG12, [ 12 ] TCONS_l2_00002973, [ 13 ] MALAT1, [ 14 , 15 ] KDM5B, [ 16 ] ANRIL, [ 17 ] AFAP1-AS1, [ 18 ] ARNILA, [ 19 ] AWPPH, [ 20 ] DANCR, [ 21 , 22 ] GAS5, [ 23 , 24 ] ZEB2-AS1, [ 23 , 24 ] ADPGK-AS1, [ 26 ] POU3F3, [ 27 ] HIF1A-AS2, [ 28 ] MAPT-AS1, [ 29 ] NEF, [ 30 ] LUCAT1, [ 31 ] LINC00511, [ 32 ] HOTAIR, [ 33 , 34 ] MIR503HG, [ 35 ] LncKLHDC7B, [ 36 ] HULC, [ 37 ] linc-ZNF469–3, [ 38 ] NAMPT-AS, [ 39 ] LINC00173, [ 40 ] and HOST2. [ 41 ] Among the included studies, 29 studies were conducted in China, while the other 2 were performed in Mexico and Italy, respectively.…”
Section: Resultsmentioning
confidence: 99%